Plasma glutamine levels before cardiac surgery are related to post-surgery infections; an observational study. Issue 1 (December 2016) - Buter, Hanneke; Koopmans, Matty; Kemperman, Ramses; Jekel, Lilian; Boerma, Christiaan
Abstract Background A low plasma glutamine level was found in 34% of patients after elective cardiothoracic surgery. This could be a result of the inflammation caused by surgical stress or the use of extracorporeal circulation (ECC). But it is also possible that plasma glutamine levels were already lowered before surgery and reflect an impaired metabolic state and a higher likelihood to develop complications. In the present study plasma glutamine levels were measured before and after cardiac surgery and we questioned whether there is a relation between plasma glutamine levels and duration of ECC and the occurrence of postoperative infections. Methods We performed a single-centre prospective, observational study in a closed-format, 20-bed, mixed ICU in a tertiary teaching hospital. We included consecutive patients after elective cardiac surgery with use of extracorporeal circulation. Blood samples were collected on the day prior to surgery and at admission on the ICU. The study was approved by the local Medical Ethics Committee (Regional Review Committee Patient-related Research, Medical Centre Leeuwarden, nWMO 115, April 28th 2015). Results Ninety patients were included. Pre-operative plasma glutamine level was 0.42 ± 0.10 mmol/l and post-operative 0.38 ± 0.09 mmol/l (p  < 0.001). There was no relation between duration of extracorporeal circulation or aortic occlusion time and changes in plasma glutamine levels. A logistic regression analysis showed a significant correlation between the presence of a positive culture during the post-operative course and pre-operative plasma glutamine levels (p  = 0.04). Conclusion Plasma glutamine levels are significantly lower just after cardiac surgery compared to pre-operative levels. We did not find a relation between the decrease in plasma glutamine levels and the duration of extracorporeal circulation or aortic clamp time. There was a correlation between pre-operative plasma glutamine levels and the presence of a positive culture after cardiac surgery. Trial registration ClinicalTrials.gov, numberNCT02444780 .